On the implementation and validation of a three‐dimensional pressure‐dependent bounding surface plasticity model for soil nonlinear wave propagation and soil‐structure interaction analyses. (4th February 2021) - Zhang, Wenyang; Lim, Keng‐Wit; Ghahari, S. Farid; Arduino, Pedro; Taciroglu, Ertugrul
Abstract: Numerous experiments and prior analyses have confirmed that soil inelasticity, which is known to come into effect even at very low strain levels, can significantly affect site response and dynamic soil‐structure interaction (SSI) behavior. To date, only a few studies were able to consider multi‐axial wave propagation problems with appropriate models of soil nonlinearity. Most existing works are limited to either homogeneous soil configurations or equivalent linear soil models. The instances wherein soil nonlinearity is accurately considered have been confined to single element tests and one‐dimensional problems. In this study, an improved pressure‐dependent bounding surface plasticity soil model—with appropriate plastic strain rate direction definition and overshooting correction scheme—is implemented in Abaqus, and validated using recordings from both the Lotung borehole array and centrifuge test data on embedded flexible structures. The implemented model is capable of comprehensively reproducing complex soil behaviors, such as stiffness degradation, damping, dilatancy, and compaction while under a wide strain range, and under general loading conditions using only a few material parameters to be calibrated. Consequently, numerically predicted results are observed to be in better agreement with experimentally measured data, in comparison with linear and another plasticity model, which include accelerations, and bending and hoop strains along the walls of the specimen structures, for low‐ as well as high‐amplitude input motions.